PEMBENTUKAN PEMERINTAHAN DARURAT REPUBLIK INDONESIA TAHUN 1948-1949 DALAM PERSPEKTIF FIQH SIYASAH DAN HUKUM TATA NEGARA - Hilmatiar, Moch. H. Kharismulloh (UIN Sunan Kalijaga Yogyakarta, 2015)
The formation of an emergency government of the Republic of Indonesia came from the Second Dutch Military Aggression on December 19, 1948 in Yogyakarta. In the aggression, President Sukarno and Vice President Mohammad Hatta taken prisoner by Dutch soldiers, causing a vacuum and paralysis of government. Before the Dutch prisoner, president has gave the a mandate to Sjafruddin prawiranegara, to form the Emergency Government, if the central government when it can no longer pass on its obligations. Sjafruddin prawiranegara located in Bukit Tinggi when the Dutch attack waged, not aware of the mandate, due to disruption of communication between Yogyakarta and Bukit Tinggi as a result of the Dutch attack. After knowing for sure captivity, then together civilian and military leaders in Central Sumatra, sjafruddin prawiranegara established the Emergency Government dated December 22, 1948. This study will discuss the PDRI according to the concept of the emergency state in perspective of fiqh siyasah and Constitutional Law. This study shows that the Emergency Government has played an important role in the framework of the struggle and the state administration during the Indonesian nation to maintain the independence of the Dutch Military Aggression II, especially in defending the existence of the Republic of Indonesia. Emergency Government struggle is inseparable from the process between diplomacy and the armed struggle, it is the process of the struggle waged to achieve the Emergency Government of the Republic of Indonesia sovereign. While legally, both from the perspective of the concept siyasah harbiyah in fiqh siyasah and Law of the State of Emergency in Constitutional Law, sjafruddin prawiranegara who served as Chairman of the Emergency Government between December 19, 1948 to the date of July 13, 1949 entitled referred to as the President of the Republic of Indonesia in emergencies.